Colonic Endometriosis Mimicking Colon Cancer on a Virtual Colonoscopy Study: A Potential Pitfall in Diagnosis - Jonathan D. Samet; Karen M. Horton; Elliot K. Fishman; Ralph H. Hruban (Case Reports in Medicine)
Colonic endometriosis has been reported in the literature to mimic colon cancer. Patients can present with symptoms almost identical to colon cancer. We present an exemplary case of a woman who was found to have a mass on conventional colonoscopy. Virtual colonoscopy was instrumental in characterizing the obstructive sigmoid mass. A biopsy of the mass revealed sigmoid endometriosis.